Political Changes in Albania and Macedonia under European Union Progress - Zejneli, Ismail; Dumi, Alba (Richtmann Publishing, 2012)
The topic on the current integration phase of the Republic of Macedonia after the completion of the questionnaire andthe commencement of the ratification process of the Stabilization-Association Agreement between the Republic of Macedoniaand the European Commission by national assemblies of the EU member states. In this phase, institutional reforms arefundamental and within those the establishment of a new modern, functional, democratic European administration is a crucialpre-condition. Since 1991, and especially after the endorsement of the Ohrid Framework Agreement in 2001, Macedonia hasbeen clearly and unambiguously determined to pursue the strategic orientation in order to integrate in the EU. After theendorsement of the Ohrid Framework Agreement, Macedonia has undergone a long and complex way of reforms towards itsEuropean integration goal. Some of the steps include the Stabilization and Association Process, endorsement of the Stabilizationand Association Agreement and the accomplishment of the application questionnaire as a candidate country for EUmembership. The country is currently going through a phase of two parallel processes that converge to the country’s fullmembership in the EU: the process of ratification of the Integration Agreement between Macedonia and the EC as well as theprocess of implementation of remaining reforms in order to accomplish the whole set of membership criteria.